Scattering of photons by an external gravitational field in the framework of higher-derivative gravity - Accioly, A.; Azeredo, A.; Mukai, H.; Neto, E. D. (Progress Theoretical Physics Publication Office, 2000)
The scattering of photons by a static gravitational field, treated as an external field, is discussed in the context of gravity with higher derivatives. It is shown that the R-2 sector of the theory does not contribute to the photon scattering, whereas the R-mu nu(2) sector produces dispersive (energy-dependent) photon propagation.